2022
DOI: 10.1159/000528351
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Constitutes an Early Sign of Acute Hypoglycemia

Abstract: <b><i>Introduction:</i></b> Research in humans has identified a link between hypoglycemia and anxiety. The present study examined anxiety-like behaviors in rats that were subjected to hypoglycemia that was produced by an acute injection of insulin. Healthy female Wistar rats were subjected to a battery of tests to explore anxiety (elevated plus maze) and locomotion (open field test). <b><i>Methods:</i></b> The control (CT) group received 0.9% saline (3 mL/kg, p.o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…This suggests that glycemia may be more related to anxiety, with anxiety driving the associations between the interaction of HbA1c with anxiety and depression and FCs. Animal studies have shown that hypoglycemia triggers anxiety-like behaviors [55]. Most likely, the increase in anxiety with hypoglycemia promotes glucose consumption.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that glycemia may be more related to anxiety, with anxiety driving the associations between the interaction of HbA1c with anxiety and depression and FCs. Animal studies have shown that hypoglycemia triggers anxiety-like behaviors [55]. Most likely, the increase in anxiety with hypoglycemia promotes glucose consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have proved that hypoglycemia induces anxiety-like behaviors in mice, with less time spent in the open arms and fewer arm entries in the EPM. 20 Our results showed that the proportion of open arms active distance in the SD + HG group ( p = 0.0449) was significantly lower than that in the control group. However, KD-fed mice, including the KD + HG group and KAb + HG group, showed significant increases in the proportion of the open arm active distance (KD + HG, p = 0.0123; KAb + HG, p = 0.0002, Fig.…”
Section: Kd Alleviated Anxiety-like Behaviors Induced By Hypoglycemia...mentioning
confidence: 48%